A Study of Sugarcane Bagasse and Wood Dust as Acoustic Panel in Building - Muhamad Isa, Nabil; Abdul Wahid, Abdul Zaki (Progress in Engineering Application and Technology, 2021)
Sugarcane bagasse and wood dust are a positive front on natural fibre-sound insulation panels study. Into the matrix, wood dust is added to protect the pores. This work involves identifying the sugarcane bagasse to absorb sound, assess and obtain sound absorption data from sugarcane bagasse and wood dust. This acoustic panel also uses natural binder that is starch flour to bind both materials and will result in a discovery of natural acoustic panels. Study technique for the preparing and production of the acoustic panel includes frame planning, sugarcane bagasse fibre, wood dust and sound analysis. The samples are divided into three, with separate sugarcane bagasse, wood dust, and binder ratios. Each of the material must be combined by hand with determining weight-based proportions. The mixture is then set in a mould and ready to print. It must press with the hot press with 150ᵒC in 6 minutes with pressure 1.0 tonne. After that, let it cool in 1 hour. Testing involves 3 types. The panel were testing physically, thermal conductivity and acoustical